Chitosan graft modified bio-based nylon material as well as preparation method and application thereof

By reacting bio-based nylon salt with chitosan quaternary ammonium salt under a protective atmosphere, chitosan grafted modified bio-based nylon material was prepared, which solved the problems of insufficient antibacterial properties and poor mechanical properties of existing bio-based nylon materials, and achieved improvement in antibacterial properties and improvement in mechanical properties of the materials. It is suitable for medical, food packaging and other fields.

CN119552354AActive Publication Date: 2025-03-04INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411802115.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-04
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The existing bio-based nylon materials have insufficient antibacterial properties and poor mechanical properties and shape stability under high temperature conditions, which limits their application in medical, food packaging and other fields.

Method used

Chitosan grafted modified biomass nylon material was prepared by mixing biomass nylon salt, water, catalyst and chitosan quaternary ammonium salt under a protective atmosphere, and performing prepolymerization and final polymerization. This method increases the antibacterial properties of the material and improves its mechanical properties and high temperature resistance.

Benefits of technology

The obtained chitosan grafted modified biomass nylon material has excellent antibacterial properties, can effectively inhibit the growth of a variety of bacteria, and has good biocompatibility, processing performance and high temperature resistance, which broadens its application in medical, food packaging and other fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer material modification, and provides a chitosan graft modified bio-based nylon material as well as a preparation method and application thereof. The preparation method comprises the following steps: under a protective atmosphere, mixing bio-based nylon salt, water, a catalyst and chitosan quaternary ammonium salt, and sequentially carrying out prepolymerization reaction and final polymerization reaction to obtain the chitosan grafted modified bio-based nylon material. Chitosan quaternary ammonium salt is selected to react with bio-based nylon salt, the number of positive charges on the surface of original polyamide is increased, a large number of positive charges can promote flocculation between polyamide and protein, teichoic acid, lipopolysaccharide and the like with negative charges on the surfaces of bacterial cells, and then the permeation barrier effect of a cytoplasmic membrane is destroyed; the integrity of thallus cells is damaged, and nutrient substances are lost, so that the intrinsic bacteriostasis effect is achieved. The chitosan graft modified bio-based nylon material obtained by the invention has excellent antibacterial performance, mechanical property and high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material modification, and in particular to a chitosan grafted modified bio-based nylon material and a preparation method and application thereof. Background Art

[0002] Existing bio-based nylon materials have the advantages of environmental protection and renewability, but their antibacterial properties are insufficient, which limits their application in the fields of medical treatment and food packaging. Chitosan has excellent biocompatibility, blood compatibility, safety and microbial degradability, and is widely used in the fields of medicine, food, chemical industry, cosmetics, water treatment and metal extraction and recovery. Grafting chitosan onto bio-based nylon materials is expected to improve the antibacterial properties of bio-based nylon materials. However, in the preparation process, there are problems such as the compatibility of chitosan and bio-based nylon, the controllability of grafting polymerization, and the stability and durability of antibacterial function. In order to overcome these problems, it is necessary to strengthen the study of the interaction mechanism between chitosan and bio-based nylon, optimize the conditions and parameters of grafting polymerization, and explore more stable and durable ways to achieve antibacterial function. On the other hand, compared with metals or other engineering plastics, nylon is often not the best choice in applications that require high tensile bending or torsional rigidity; in addition, under high temperature conditions, nylon is very easy to soften or melt, thereby losing its original mechanical properties and shape stability. Therefore, improving the mechanical properties and high temperature resistance of nylon is also a problem to be solved. In summary, it is of great significance to provide a new method for preparing chitosan grafted modified bio-based nylon materials, thereby obtaining a modified bio-based nylon material with excellent antibacterial properties, good mechanical properties and high temperature resistance. Summary of the invention

[0003] The purpose of the present invention is to overcome the problems existing in the prior art and provide a chitosan grafted modified bio-based nylon material and a preparation method and application thereof.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a chitosan grafted modified bio-based nylon material, comprising the following steps:

[0006] Under a protective atmosphere, bio-based nylon salt, water, a catalyst and chitosan quaternary ammonium salt are mixed, and a prepolymerization reaction and a final polymerization reaction are carried out in sequence to obtain the chitosan grafted modified bio-based nylon material.

[0007] Preferably, the bio-based nylon salt includes nylon 56 salt, nylon 54 salt, nylon 510 salt, nylon 512 salt or nylon 513 salt.

[0008] Preferably, the catalyst includes sodium hydroxide, toluene diisocyanate, a titanium-based catalyst, a phosphorus-containing compound or a boric acid compound.

[0009] Preferably, the chitosan quaternary ammonium salt is hydroxypropyltrimethylammonium chloride chitosan, and the deacetylation degree of the hydroxypropyltrimethylammonium chloride chitosan is 97-99%.

[0010] Preferably, the mass ratio of nylon salt, water, catalyst and chitosan quaternary ammonium salt is 80-100:50-70:0.3-0.5:2-8.

[0011] Preferably, the mixing temperature is 45-55° C., the mixing pressure is 8-12 kPa, and the mixing time is 0.3-0.7 h.

[0012] Preferably, the temperature of the prepolymerization reaction is 150-200° C., the pressure of the prepolymerization reaction is 5-9 kPa, and the time of the prepolymerization reaction is 1-8 hours.

[0013] Preferably, the temperature of the final polymerization reaction is 210-280° C., the vacuum degree of the final polymerization reaction is 0.005-0.015 MPa, and the time of the final polymerization reaction is 1-8 hours.

[0014] The invention also provides the chitosan grafted modified bio-based nylon material prepared by the preparation method of the chitosan grafted modified bio-based nylon material.

[0015] The invention also provides application of the chitosan grafted modified bio-based nylon material in medical product packaging or food packaging.

[0016] The beneficial effects of the present invention are:

[0017] The present invention provides a preparation method of a chitosan grafted modified bio-based nylon material, comprising the following steps: mixing bio-based nylon salt, water, a catalyst and chitosan quaternary ammonium salt under a protective atmosphere, and sequentially performing a prepolymerization reaction and a final polymerization reaction to obtain a chitosan grafted modified bio-based nylon material. The present invention selects chitosan quaternary ammonium salt to react with the bio-based nylon salt, thereby increasing the number of positive charges on the surface of the original polyamide. A large amount of positive charges can promote flocculation of the polyamide with negatively charged proteins, teichoic acid, lipopolysaccharides, etc. on the surface of bacterial cells, thereby destroying the permeability barrier of the cytoplasmic membrane, resulting in the destruction of the integrity of the bacterial cells and the loss of nutrients, thereby achieving the effect of intrinsic antibacterial. The chitosan grafted modified bio-based nylon material obtained by the preparation method of the present invention has excellent antibacterial properties and can effectively inhibit the growth of various bacteria; and the modified bio-based nylon material also has good biocompatibility and can be applied to the fields of medical supplies packaging or food packaging; at the same time, the chitosan grafted modified bio-based nylon material is environmentally friendly and renewable, has good processing properties, and is easy to be made into products of various shapes; in addition, the mechanical properties and high temperature resistance of the chitosan grafted modified bio-based nylon material obtained by the preparation method of the present invention are also significantly improved, broadening its application in high temperature resistance and tensile bending resistance. DETAILED DESCRIPTION

[0018] The present invention provides a method for preparing a chitosan grafted modified bio-based nylon material, comprising the following steps:

[0019] Under a protective atmosphere, bio-based nylon salt, water, a catalyst and chitosan quaternary ammonium salt are mixed, and a prepolymerization reaction and a final polymerization reaction are carried out in sequence to obtain the chitosan grafted modified bio-based nylon material.

[0020] In the present invention, the bio-based nylon salt preferably includes nylon 56 salt, nylon 54 salt, nylon 510 salt, nylon 512 salt or nylon 513 salt.

[0021] In the present invention, the method for preparing the bio-based nylon salt preferably comprises the following steps:

[0022] In a nitrogen atmosphere, pentamethylenediamine, aliphatic dibasic acid and a solvent are mixed and reacted to obtain a bio-based nylon salt solution; the bio-based nylon salt solution is purified to obtain a bio-based nylon salt.

[0023] In the present invention, the aliphatic dibasic acid preferably includes adipic acid, succinic acid, sebacic acid, dodecanedioic acid or tridecanedioic acid; and the solvent is preferably ethanol or water.

[0024] In the present invention, when the aliphatic dibasic acid is adipic acid, the bio-based nylon salt is nylon 56 salt; when the aliphatic dibasic acid is succinic acid, the bio-based nylon salt is nylon 54 salt; when the aliphatic dibasic acid is sebacic acid, the bio-based nylon salt is nylon 510 salt; when the aliphatic dibasic acid is dodecanedioic acid, the bio-based nylon salt is nylon 512 salt; when the aliphatic dibasic acid is tridecanedioic acid, the bio-based nylon salt is nylon 513 salt.

[0025] In the present invention, the mass ratio of pentamethylenediamine, aliphatic dibasic acid and solvent is preferably 60-100:25-50:10-30, more preferably 70-90:30-45:15-25, and more preferably 80-80.9:35-38.83:20-22.

[0026] In the present invention, the reaction is preferably carried out in a water bath, the reaction temperature is preferably 30-120°C, more preferably 40-80°C, more preferably 55-60°C; the reaction time is preferably 0.5-2h, more preferably 0.75-1.5h, more preferably 1h.

[0027] In the present invention, the catalyst preferably includes sodium hydroxide, toluene diisocyanate, a titanium catalyst, a phosphorus-containing compound or a boric acid compound; the titanium catalyst is preferably titanium dioxide; the phosphorus-containing compound preferably includes phosphoric acid, phosphorous acid, hypophosphorous acid, sodium hypophosphite, sodium hypophosphite, alkyl-substituted phosphoric acid, aryl-substituted phosphoric acid, aryl-substituted hypophosphorous acid, phosphorus-containing alkanes, phosphorus-containing aryl ester compounds, phosphorus-containing metal salts or phosphorus-containing ammonium salts; the boric acid compound is preferably boric acid; the present invention does not limit alkyl-substituted phosphoric acid, aryl-substituted phosphoric acid, aryl-substituted hypophosphorous acid, phosphorus-containing alkanes, phosphorus-containing aryl ester compounds, phosphorus-containing metal salts, phosphorus-containing ammonium salts, and the common compounds in the art can be used.

[0028] In the present invention, the chitosan quaternary ammonium salt is preferably hydroxypropyl trimethyl ammonium chloride chitosan, and the deacetylation degree of the hydroxypropyl trimethyl ammonium chloride chitosan is preferably 97-99%, more preferably 97.5-98.5%, and more preferably 98%; the hydroxypropyl trimethyl ammonium chloride chitosan is preferably purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0029] In the present invention, the mass ratio of nylon salt, water, catalyst and chitosan quaternary ammonium salt is preferably 80-100:50-70:0.3-0.5:2-8, more preferably 85-95:55-65:0.35-0.45:3-7, and more preferably 90:59.6:0.45:4-5.

[0030] In the present invention, the protective atmosphere is preferably a nitrogen atmosphere; the setting of the nitrogen atmosphere preferably comprises the following steps: after adding the raw materials into the polymerization reactor, sealing the polymerization reactor, purging with nitrogen, replacing the air in the reactor 5 times, the input pressure of the nitrogen during purging is preferably 1-2MPa, more preferably 1.2-1.8MPa, more preferably 1.5MPa; then reducing the pressure to the mixing pressure, performing mixing and subsequent prepolymerization reaction and final polymerization reaction.

[0031] In the present invention, the mixing temperature is preferably 45-55°C, more preferably 47-53°C, and more preferably 50°C; the mixing pressure is preferably 8-12kPa, more preferably 9-11kPa, and more preferably 10kPa; the mixing time is preferably 0.3-0.7h, more preferably 0.4-0.6h, and more preferably 0.5h.

[0032] In the present invention, the temperature of the prepolymerization reaction is preferably 150-200°C, more preferably 160-190°C, more preferably 170-180°C; the pressure of the prepolymerization reaction is preferably 5-9kPa, more preferably 6-8kPa, more preferably 7-7.3kPa; the time of the prepolymerization reaction is preferably 1-8h, more preferably 2-7h, more preferably 3-6h.

[0033] In the present invention, after the prepolymerization reaction is completed, the pressure relief valve on the reactor is opened to discharge water vapor and other low-boiling point substances until the vacuum degree reaches the vacuum degree of the final polymerization reaction, the pressure relief valve is closed, and the temperature is raised to the temperature of the final polymerization reaction to carry out the final polymerization reaction. After the final polymerization reaction is completed, vacuum is drawn to obtain the chitosan grafted modified bio-based nylon material.

[0034] In the present invention, the temperature of the final polymerization reaction is preferably 210-280°C, more preferably 220-270°C, and more preferably 230-260°C; the vacuum degree of the final polymerization reaction is preferably 0.005-0.015MPa, more preferably 0.008-0.012MPa, and more preferably 0.01MPa; the time of the final polymerization reaction is preferably 1-8h, more preferably 2-7h, and more preferably 3-6h; after the final polymerization reaction is completed, the reaction is evacuated to the target vacuum degree, and the target vacuum degree is preferably 0.005-0.015MPa, more preferably 0.008-0.012MPa, and more preferably 0.01MPa.

[0035] The invention also provides the chitosan grafted modified bio-based nylon material prepared by the preparation method of the chitosan grafted modified bio-based nylon material.

[0036] The invention also provides application of the chitosan grafted modified bio-based nylon material in medical product packaging or food packaging.

[0037] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0038] Example 1

[0039] In a nitrogen atmosphere, pentamethylenediamine, sebacic acid and water (the mass ratio of pentamethylenediamine, sebacic acid and water is 80.9:38.83:20) are mixed and heated in a water bath at 55°C for 0.5h to obtain a nylon 510 salt solution; the nylon 510 salt solution is purified to obtain nylon 510 salt; 90g of nylon 510 salt, 59.6g of water and 0.45g of sodium hypophosphite are mixed to obtain a salt solution, which is placed in a polymerization reactor, and then 2g of hydroxypropyltrimethylammonium chloride chitosan (with a deacetylation degree of 98%) is added thereto, the polymerization reactor is sealed, and purged with nitrogen (the input pressure of nitrogen is 1.5MPa) to replace the air in the reactor. 5 times, then reduce the pressure to 10kPa, mix at 50℃ for 0.5h, then raise the temperature to 200℃, and carry out prepolymerization at a pressure of 7.3kPa. Set the prepolymerization time to 2h. After the prepolymerization, open the pressure relief valve on the reactor to discharge water vapor and other low-boiling point substances until the vacuum degree reaches 0.01MPa, close the pressure relief valve, and raise the temperature to 270℃ for final polymerization. Set the final polymerization time to 80min. After the reaction, evacuate and adjust the vacuum degree to 0.01MPa to obtain chitosan grafted modified bio-based nylon material.

[0040] Example 2

[0041] The other conditions in Example 1 were kept unchanged, and the mass of hydroxypropyltrimethylammonium chloride chitosan was changed to 3 g to obtain a chitosan grafted modified bio-based nylon material.

[0042] Example 3

[0043] The other conditions in Example 1 were kept unchanged, and the mass of hydroxypropyltrimethylammonium chloride chitosan was changed to 4 g to obtain a chitosan grafted modified bio-based nylon material.

[0044] Example 4

[0045] The other conditions in Example 1 were kept unchanged, and the mass of hydroxypropyltrimethylammonium chloride chitosan was changed to 5 g to obtain a chitosan grafted modified bio-based nylon material.

[0046] Comparative Example 1

[0047] 0.45g chitosan was dissolved in 250mL acetic acid solution with a mass fraction of 1%, and then 6g benzaldehyde was added, and the reaction was carried out at room temperature for 24h. After the reaction was completed, 50mL sodium hydroxide solution with a mass fraction of 1% was added dropwise to precipitate, and the system was filtered, and then the obtained filter cake was washed with ethanol and deionized water in sequence to obtain Schiff base protected chitosan; 0.6g Schiff base protected chitosan was added to 100mL sodium hydroxide solution with a mass fraction of 1.5%, and 0.8g epichlorohydrin was added after stirring, and the reaction was stirred at 50°C for 6h. After the reaction was completed, the system was filtered, and the obtained filter cake was washed with ethanol and deionized water in sequence to obtain epoxidized Schiff base chitosan;

[0048] 0.2 g of epoxidized Schiff base chitosan was added to 50 mL of dimethyl sulfoxide, and stirred at 80° C. for 12 h. Then, 0.09 g of DL-aspartic acid was added, and the reaction was stirred at 95° C. for 16 h. The sample obtained by the reaction was added to 100 mL of a 3% hydrochloric acid solution, and the reaction was stirred at room temperature for 24 h. After the reaction was completed, the solvent was filtered, and the obtained product was washed with ethanol and deionized water in sequence to obtain a polycarboxyl hydrophilic modified chitosan.

[0049] The same method as in Example 1 was used to prepare nylon 510 salt;

[0050] 90g of nylon 510 salt, 60g of water and 0.45g of sodium hypophosphite were mixed to obtain a salt solution, which was placed in a polymerization reactor, and then 3g of polycarboxyl hydrophilic modified chitosan was added thereto. The polymerization reactor was sealed, purged with nitrogen (the input pressure of nitrogen was 1.5MPa), the air in the reactor was replaced 5 times, and then the pressure was reduced to 10kPa, mixed at a temperature of 50°C for 0.5h, and then heated to 200°C, and prepolymerization was carried out at a pressure of 7.3kPa, and the prepolymerization time was set to 2h. After the prepolymerization was completed, the pressure relief valve on the reactor was opened to discharge water vapor and other low-boiling point substances until the vacuum reached 0.01MPa, and the pressure relief valve was closed. At the same time, the temperature was raised to 270°C for final polymerization, and the final polymerization time was set to 80min. After the reaction was completed, vacuum was evacuated and the vacuum was adjusted to 0.01MPa to obtain a modified bio-based nylon material.

[0051] The chitosan grafted modified bio-based nylon materials prepared in Examples 1 to 4 and the modified bio-based nylon materials prepared in Comparative Example 1 were subjected to performance tests, respectively. The performance tests included an inhibition zone diameter test, a melting point test, and a tensile strength test. The method for the inhibition zone diameter test was as follows: 25 mL of agar medium was poured into sterile culture dishes in a clean bench, and the dishes were cooled and solidified naturally; a 1×10 8100 μL of Escherichia coli suspension with CFU / mL was inoculated on the culture medium and evenly smeared on the surface of the agar culture medium with a smear stick. The chitosan grafted modified bio-based nylon material prepared in Examples 1 to 4 and the modified bio-based nylon material prepared in Comparative Example 1 were respectively injection molded into circular samples of Φ6mm*1mm (1mm is the thickness of the circular sample), placed on the center surface of the agar culture medium, covered with a culture dish cover, and inverted in a 37°C incubator for 24 hours to observe the results; the tensile strength test was carried out in accordance with the national standard GB / T 1040-92 on a CMT 5104 microcomputer-controlled electronic universal testing machine (tensile rate of 20.0mm / min, experimental temperature of 18°C). Through the above tests, the performance test results of the chitosan grafted modified bio-based nylon material in Examples 1 to 4 and the modified bio-based nylon material in Comparative Example 1 were obtained, as shown in Table 1.

[0052] Table 1 Performance test results of chitosan grafted modified bio-based nylon materials in Examples 1 to 4 and modified bio-based nylon materials in Comparative Example 1

[0053] Case Diameter of inhibition zone (mm) Melting point(℃) Tensile strength(MPa) Example 1 5.8±0.2 258.9 76 Example 2 6.2±0.2 268.7 82 Example 3 6.1±0.2 265.0 81 Example 4 5.9±0.2 257.6 74 Comparative Example 1 2.0±0.2 245.0 67

[0054] It can be seen from Table 1 that with the increase in the amount of hydroxypropyltrimethylammonium chloride chitosan, the antibacterial effect, tensile strength and melting point of the chitosan grafted modified bio-based nylon material all show a trend of first increasing and then decreasing. The chitosan grafted modified bio-based nylon material obtained in Example 2 has the best antibacterial effect and tensile strength, and the highest melting point; after replacing hydroxypropyltrimethylammonium chloride chitosan with polycarboxyl hydrophilic modified chitosan, the various properties of the modified bio-based nylon material are significantly reduced.

[0055] As can be seen from the above embodiments, the present invention provides a method for preparing a chitosan grafted modified bio-based nylon material, comprising the following steps: mixing bio-based nylon salt, water, a catalyst and chitosan quaternary ammonium salt under a protective atmosphere, and sequentially performing a prepolymerization reaction and a final polymerization reaction to obtain a chitosan grafted modified bio-based nylon material. The present invention selects chitosan quaternary ammonium salt to react with bio-based nylon salt, thereby increasing the number of positive charges on the surface of the original polyamide. A large amount of positive charges can promote flocculation of polyamide with negatively charged proteins, teichoic acid, lipopolysaccharides, etc. on the surface of bacterial cells, thereby destroying the permeability barrier of the cytoplasmic membrane, resulting in the destruction of the integrity of the bacterial cells and the loss of nutrients, thereby achieving the effect of intrinsic antibacterial. The chitosan grafted modified bio-based nylon material obtained by the preparation method of the present invention has excellent antibacterial properties and can effectively inhibit the growth of various bacteria; and the modified bio-based nylon material also has good biocompatibility and can be applied to the fields of medical supplies packaging or food packaging; at the same time, the chitosan grafted modified bio-based nylon material is environmentally friendly and renewable, has good processing properties, and is easy to be made into products of various shapes; in addition, the mechanical properties and high temperature resistance of the chitosan grafted modified bio-based nylon material obtained by the preparation method of the present invention are also significantly improved, broadening its application in high temperature resistance and tensile bending resistance.

[0056] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a chitosan grafted modified bio-based nylon material, characterized in that: It includes the following steps: Under a protective atmosphere, bio-based nylon salt, water, a catalyst and chitosan quaternary ammonium salt are mixed, and a prepolymerization reaction and a final polymerization reaction are carried out in sequence to obtain the chitosan grafted modified bio-based nylon material.

2. The method for preparing the chitosan grafted modified bio-based nylon material according to claim 1, characterized in that: The bio-based nylon salt includes nylon 56 salt, nylon 54 salt, nylon 510 salt, nylon 512 salt or nylon 513 salt.

3. The method for preparing the chitosan grafted modified bio-based nylon material according to claim 2, characterized in that: The catalyst includes sodium hydroxide, toluene diisocyanate, a titanium catalyst, a phosphorus-containing compound or a boric acid compound.

4. The method for preparing the chitosan grafted modified bio-based nylon material according to claim 3, characterized in that: The chitosan quaternary ammonium salt is hydroxypropyl trimethyl ammonium chloride chitosan, and the deacetylation degree of the hydroxypropyl trimethyl ammonium chloride chitosan is 97-99%.

5. The method for preparing the chitosan grafted modified bio-based nylon material according to claim 4, characterized in that: The mass ratio of nylon salt, water, catalyst and chitosan quaternary ammonium salt is 80-100:50-70:0.3-0.5:2-8.

6. The method for preparing the chitosan grafted modified bio-based nylon material according to claim 5, characterized in that: The mixing temperature is 45-55° C., the mixing pressure is 8-12 kPa, and the mixing time is 0.3-0.7 h.

7. The method for preparing the chitosan grafted modified bio-based nylon material according to claim 6, characterized in that: The temperature of the prepolymerization reaction is 150-200° C., the pressure of the prepolymerization reaction is 5-9 kPa, and the time of the prepolymerization reaction is 1-8 hours.

8. The method for preparing the chitosan grafted modified bio-based nylon material according to claim 7, characterized in that: The temperature of the final polymerization reaction is 210-280° C., the vacuum degree of the final polymerization reaction is 0.005-0.015 MPa, and the time of the final polymerization reaction is 1-8 hours.

9. The chitosan grafted modified bio-based nylon material prepared by the method for preparing the chitosan grafted modified bio-based nylon material according to any one of claims 1 to 8.

10. Use of the chitosan grafted modified bio-based nylon material according to claim 9 in medical product packaging or food packaging.

Citation Information

Patent Citations

  • Preparation method of 2-hydroxypropyltrimethyl ammonium chloride chitosan

    CN101613420A

  • Long-acting antibacterial bio-based nylon resin and preparation method thereof

    CN114196011A

  • Chitosan quaternary ammonium salt grafted starch antibacterial preservative film as well as preparation method and application thereof

    CN116925360A

  • Antimicrobial fabrics through surface modification

    US20030159200A1